2001
DOI: 10.1093/fampra/18.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing in acute infections of the nose or sinuses: a matter of personal habit?

Abstract: Whether or not a patient with an acute infection of the nose and/or sinuses will be handed an antibiotic prescription seems to depend more on the attending doctor's prescribing behaviour than on the clinical picture. Further qualitative research into attitudes which may be related to a high tendency to prescribe antibiotics consequently is of the utmost importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 4 publications
6
55
1
Order By: Relevance
“…Individual clinician prescribing habits, rather than clinical presentation, have been shown to best predict antibiotic prescription, 25 and these habits tend to remain stable over time. 26 Given that trainees come to resemble their supervisors, the problem of antibiotic overprescription will not decrease in the future without intervention.…”
Section: 24mentioning
confidence: 99%
“…Individual clinician prescribing habits, rather than clinical presentation, have been shown to best predict antibiotic prescription, 25 and these habits tend to remain stable over time. 26 Given that trainees come to resemble their supervisors, the problem of antibiotic overprescription will not decrease in the future without intervention.…”
Section: 24mentioning
confidence: 99%
“…6 Antibiotic prescribing for upper respiratory tract infections is related to a defensive attitude of the family physician. 7 Doctors feeling pressured by their patients to prescribe an antibiotic is an important factor that leads to overprescribing. [8][9][10][11] Several studies have shown, however, that patients' expectations are often not made explicit during the offi ce visit 13 and correlate poorly with the physician's perceptions of these expectations.…”
Section: Introductionmentioning
confidence: 99%
“…23 Others found the same association, [24][25][26] which may be explained as follows: patients generally know the prescription pattern of their GP and this may, in turn, affect GP consultation rates. However, in contrast to these studies, the current study combined both patient viewpoints with respect to a specific respiratory tract infection and GP characteristics.…”
Section: Comparison With Existing Literaturementioning
confidence: 92%